Transformasi Pendidikan Agama Islam di Madrasah Menuju Pendidikan yang Holistik dan Relevan Dengan Tuntutan Zaman - Fauzan, M.; Aprison, Wedra; Rahmadhani, Riri (Universitas Pahlawan Tuanku Tambusai, 2024)
Transformation in Islamic religious learning is an urgent need in an era that continues to develop. This article highlights fundamental changes in PAI learning towards a learning approach that is holistic and relevant to today's demands. Focusing on the context of Islamic religious education, this article discusses the challenges and opportunities in integrating Islamic values with rapidly changing social, technological and cultural contexts. By exploring holistic concepts and relevance, this article proposes strategies and methods for developing Islamic religious learning that reaches aspects of modern life in depth. This transformation not only strengthens understanding of religion, but also equips students with the skills and understanding needed to face the complexity of today's world.